Rapid Improvement in Passive Tuberculosis Case Detection and Tuberculosis Treatment Outcomes After Implementation of a Bundled Laboratory Diagnostic and On-Site Training Intervention Targeting Mid-Level Providers. (6th March 2015) - Manabe, Yukari C.; Zawedde-Muyanja, Stella; Burnett, Sarah M.; Mugabe, Frank; Naikoba, Sarah; Coutinho, Alex
Abstract: Background.  Tuberculosis (TB) control is a public health priority with 3 million cases unrecognized by the public health system each year. We assessed the impact of improved TB diagnostics and on-site training on TB case detection and treatment outcomes in rural healthcare facilities. Methods.  Fluorescence microscopy, Xpert MTB/RIF, and on-site training were introduced at 10 healthcare facilities. Using quasi-experimental methods, these 10 intervention healthcare facilities were compared with 2 controls and their own performance the previous year. Results.  From January to October 2012, 186 357 and 32 886 outpatients were seen in the 10 intervention and 2 control facilities, respectively. The intervention facilities had a 52.04% higher proportion of presumptive TB cases with a sputum examination (odds ratio [OR] = 12.65; 95% confidence interval [CI], 5.60–28.55). After adjusting for age group and gender, the proportion of smear-positive patients initiated on treatment was 37.76% higher in the intervention than in the control facilities (adjusted OR [AOR], 7.59; 95% CI, 2.19–26.33). After adjusting for the factors above, as well as human immunodeficiency virus and TB retreatment status, the proportion of TB cases who completed treatment was 29.16% higher (AOR, 4.89; 95% CI, 2.24–10.67) and the proportion of TB cases who were lost to follow-up was 66.98% lower (AOR, 0.04; 95% CI, 0.01–0.09). When compared with baseline performance, the intervention facilities had a significantly higher proportion of presumptive TB cases with a sputum examination (64.70% vs 3.44%; OR, 23.95; 95% CI, 12.96–44.25), and these facilities started 56.25% more smear-positive TB cases on treatment during the project period (AOR, 15.36; 95% CI, 6.57–35.91). Conclusions.  Optimizing the existing healthcare workforce through a bundled diagnostics and on-site training intervention for nonphysician healthcare workers will rapidly improve TB case detection and outcomes towards global targets.